A cross-sectional observational drug utilisation study of antipsychotic drugs prescribed in patients suffering from psychiatric illnesses at a tertiary care hospital - Pal, Amitrajit; Gambre, Rohini (International Journal of Basic & Clinical Pharmacology, 2022)
Background: The rapidly expanding field of psychopharmacotherapy is challenging the traditional concepts of psychiatric treatment and research and is constantly seeking new and improved drugs to treat psychiatric disorders. Methods: The present study was undertaken to analyse the pattern of drug utilization of antipsychotic medications in outdoor patients of psychiatry department of a tertiary care hospital. 600 prescriptions of 600 patients suffering from different psychiatric illnesses were taken for analyses in which antipsychotic agents were prescribed either as a main drug or as a concomitant agent after proper taking written informed consent. Results: A total of 1681 drugs were prescribed in our study population The average number of drugs prescribed per prescription in the study population was 2.61±1.32. Schizophrenia, bipolar disorder, depression were among the most common illnesses for which antipsychotics were prescribed. Atypical antipsychotics were most commonly prescribed in the study population out of which olanzapine was prescribed in most of the patients. Considering the cost analysis of the present study, the average cost per prescription was 475.02 INR. Average cost of antipsychotics per prescription was 208.1 INR. Conclusions: The present study provides valuable insight into the overall pattern of antipsychotic drugs prescribed in patients suffering from different psychiatric illnesses and mental health disorders and the principles of rational prescribing were followed in accordance with the various drug use indicators mentioned by WHO.